Literatur Review : Terapy Musik Terhadap Hipertensi Kehamilan - Ahmaniyah Ahmaniyah; Ratna Indriyani (Fakultas Ilmu Kesehatan, 2020)
Abstract Hypertension in pregnancy is a complication of pregnancy in general, which affects 2% of pregnant women in the world. And is a cause of death of pregnant women in the world, the handling of hypertension is done conventionally, namely hypertension-lowering drugs, but this conventional treatment has many obstacles because it is related to pregnant women who will certainly be related because it is related to pregnant women who will definitely be related to the fetus. Objective: to analyze which music therapy is most effective in reducing blood pressure in pregnant women who have hypertension. Method: This research was reviewed from an electronic database including Science Direct, Pubmed, Google Scholar and other related websites. With the keywords